Terahertz Dual-Band Antennas Using Step Impedance Resonators With Coplanar Waveguides for Subwavelength Wireless Networks - Kola Thirupathaiah; Montasir Qasymeh (IEEE Access, 2024)
This paper introduces the design, investigation, and evaluation of ultra-compact, nanoplasmonic, concurrent dual-band antennas. Utilizing step impedance resonators (SIRs) based on metal-insulator-metal (MIM) waveguide components, we designed the operating frequencies to be centered around 187 THz and 230 THz. The proposed antennas are implemented using symmetrical coplanar waveguide (CPW) components with silica as the insulator, sandwiched between silver metallic layers. We demonstrate that incorporating the SIRs enhances control over spurious resonances compared to conventional uniform impedance resonator (UIR) designs. Using this approach, we designed three concurrent dual-band optical antennas. The first antenna (A), is designed with two simultaneous optical center frequencies at 187 THz and 230 THz with a total length ( $L = 3.830 \ μ $ m) by using two basic SIRs. The second and third antennas (B), and (C) are designed at two simultaneous center frequencies at 187 THz and 230 THz with different total lengths of the antennas ( $L = 3.820 \ μ $ m) and ( $L = 3.800 \ μ $ m), respectively. To address the radiation null issue observed in the broadside direction of antenna (A), four parasitic slot elements have been incorporated near the primary radiating resonators in the other two antennas, (B) and (C). This modification resulted in nearly omnidirectional radiation patterns at the high-order mode frequencies, thereby enhancing the performance of the antennas.